The Influence Of Recrutmen And Selection On Employe Performance Pt Meta Global Triasha (Survey Of X-Sha Outlet Singaparna Plaza Employees) - Rafiq, Fakhri Muhammad; Sutrisna, Arga; Risana, Dudu (Utami Publisher, 2025)
The purpose of this research is to determine the magnitude of the influence of recruitment and selection on PT Meta Global Triasha (X-Sha Survey Singaparna plaza) with a population or respondents of 43 employees. This research method uses explanatory research, while the sampling technique uses saturated samples. So 43 people used it. The data sources used are primary data sources and the data is collected through questionnaires, interviews and observations. in this research. This analysis tool uses multiple linear regression. In the hypothesis testing process, the Simultaneous Test (F) and Partial Test (T) are used. The research results show that in recruitment and selection, the performance of PT Meta Global Triasha X-Sha Outlet Singaparna Plaza employees has very good assessment qualifications. simultaneous recruitment and selection have a significant effect on the performance of PT Meta Global X-Sha employees (Survey of X-Sha Outlet Singaparna Plaza employees). Recruitment partially has a significant effect on the performance of employees at PT Meta Global Triasha X-Sha Singparna Plaza. Selection has a partial effect on the performance of employees at PT Meta Global Triasha.